"Lesser Citizens”: Poverty and Social Exclusion among the Juvenile Italian and European Population - Cecchi, Sergio (Italian Sociological Review, 2013)
This article deals with the spread of poverty and social exclusion throughout the juvenile, Italian population, comparing it with its European counterparts. Besides the information concerning the distribution of income in families with children, the family units’ living conditions will also be taken into consideration as well as the number of young people who are not enrolled at school, taking part on professional training courses and who are not even employed. The juvenile, Italian situation is distinctly marked, as you will see, compared to the European one, by a greater spread of poverty, poor living conditions and the simultaneous lack of work or professional training. If the families are foreign, the children’s situation is even more precarious, in view of the fact that their salaries are – in spite of performing the same duties – lower, on average, for immigrant workers. Many social factors, connected with the labour market structure and economic policy choices all, undoubtedly, contribute to this, but the Italian Welfare State’s set up is also extremely important in that it invests very little in the support of family units.